Impact of Orthognathic Surgery on Quality of Life in Patients with Dentofacial Deformities - Faezeh Eslamipour; Arash Najimi; Azade Tadayonfard; Zeinab Azamian (International Journal of Dentistry)
The aim of this investigation was to determine the impact of orthognathic surgery on quality of life in patients with dentofacial deformities at immediate presurgery and at 3-week, 3-month, and 6-month intervals following the surgery. Subjects included forty-three 18–40-year-old Iranian orthognathic patients who were referred to private offices in Isfahan. Data collection was performed using the 22-item Orthognathic Quality of Life Questionnaire (OQLQ). Participants completed the questionnaire prior to surgery and 3 weeks, 3 months, and 6 months after it. Differences and correlations were calculated by the two-tailed t-test, ANOVA with Repeated Measure test, and the Pearson correlation coefficient. The results showed significant reduction returned to baseline in OQLQ mean scores and aesthetic, awareness, and social subdomains in all 3 intervals after surgery. However oral function domain showed an increase at T2 and then a decrease at next intervals. Maximum and minimum effect size were observed in aesthetic (ES = 0.7) and oral function (ES = 0.3) domain, respectively. Based on the finding of this study, in 6-month interval after surgery, orthognathic surgery causes significant improvements in quality of life in patients with dentofacial deformities as assessed in emotional, psychological, oral function, and social domains and maximum changes occurred in emotional domain.